2019
DOI: 10.1007/s10578-019-00914-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality of Life in Children and Adolescents with Psychiatric Disorders

Abstract: This study aimed to identify factors that predict quality of life (QoL), over and above potential improvements in QoL related to a decrease in psychopathology, in children and adolescents with psychiatric problems. Two hundred and thirty one referred children and adolescents, aged 7-19 years, were followed up across a 1-year period. QoL and psychopathology were assessed, as were a broad range of child, parent, and family/social network factors. Time 1 QoL scores and change in level of psychopathology from Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The extent to which these children experience a lower mental and social health, however, varies per condition ( 13 , 14 ). For instance, the level of psychopathology, degree of stressful events, gender, and school attendance are associated with psychosocial functioning ( 15 , 16 ). Therefore, it is important to examine mental and social health during the COVID-19 lockdown in which many of these factors are involved ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which these children experience a lower mental and social health, however, varies per condition ( 13 , 14 ). For instance, the level of psychopathology, degree of stressful events, gender, and school attendance are associated with psychosocial functioning ( 15 , 16 ). Therefore, it is important to examine mental and social health during the COVID-19 lockdown in which many of these factors are involved ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…All but one study examined adults and the remaining article examined adolescents. While studies which examined QOL in children and adolescents have been conducted, these have exclusively examined children and adolescents with various physical disabilities or medical conditions such as cerebral palsy ( Makris et al, 2021 ), asthma ( Kouzegaran et al, 2018 ), traumatic brain injury ( Di Battista et al, 2012 ), disease conditions ( Wolf et al, 2018 ; Wardoku et al, 2019 ; Marschner et al, 2020 ) and trauma and mental health challenges ( Bastiaansen et al, 2020 ; Lawson et al, 2020 ; Pinto et al, 2021 ). A number of studies have examined QOL in children with autism with or without specifically identified sensory processing challenges ( Benen Demchick et al, 2014 ; Chuang et al, 2014 ; Xu et al, 2019 ; Leader et al, 2021 ; Oakley et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the studies on QOL in healthy adolescents are scarce. QOL of adolescents is a subjective measure that assesses physical and emotional functioning, social functioning, and school functioning [ 13 ]. QOL of students can predict children with potential problematic behavior and help to identify those who need help from mental health agencies.…”
Section: Introductionmentioning
confidence: 99%